"Each of Us is an Other". (December 2022) - Rodríguez García, Magaly
Abstract: Cobble's study of American social democratic feminism is a fascinating narrative of the lives of women who crossed the boundaries of class, race and nation-states to build a better world. Her chronological account of the careers and activism of these women is not only a major contribution to the history of feminism but also a significant addition to the study of social democracy worldwide.